Production of pectin from mango (Mangifera indica L.) peels a plant design - Arsitoy, Megan E.; Basis, Kevin R.; Veloso, Merrie Marriel V.
Preliminary studies were done to ensure the feasibility of the proposed plant. Today, pectin is increasingly used in the production of dairy goods due to the strong demand for yogurt products and ice cream. The lack of a local manufacturing plant of pectin in the Philippines causes all of the pectin used in the country to be imported. It is the intention of the pectin plant to produce a fraction of the countrys pectin demand and trim down the cost of pectin import. For the market analysis, the Philippines pectin import was especially put into consideration since this represent the whole local pectin demand. With an average annual increase of 4.73 metric tons in pectin demand from 2000 to 2010, and on the assumption that this increase will consistently followed in the years that follow, the Philippines demand for pectin was projected until the year 2022. The plant will produce 30% of the estimated demand by 2017, which is roughly 33.22 metric tons. Projections for the mango peel supply as well as the price of pectin were also done with the assumption of a steady average increase computed from the previous years data. The major basis for the selection of plant location was the proximity of the raw material supply. With this, the plant is to be strategically built 1.2 kilometers southwest of Profood International Corporation in Mandaue City, Cebu, where mango peels will be obtained. The production of pectin from mango peels consist of three parts - the pre-treatment process where the raw materials are readied for extraction, the extraction process pectin is leached out of the mango peels, and the purification of pectin to produce the final product. The plant will function on a steady-state continuous operation. It will operate 24 hours daily, for 350 days a year.